Węgrzy jako pars aliqua gentis Massagetum. Ślady późnoantycznej i wczesnośredniowiecznej uczoności w dziele Tomasza archidiakona Splitu. Część 2. Postrzeganie Massagetów. 2) Kontekst „huński”, 1. Hunowie-Węgrzy - Lesław Spychała (Studia Antiquitatis et Medii Aevi Incohantis)
(Hungarians as pars aliqua gentis Massagetum. Traces of erudition in the late antique and early medieval periods in the work of Archdeacon Thomas of Split. Part 2. The Perception of the Massagetean. 2) The “Hunnic” context, 1. Huns and Hungarians): Thomas of Split is considered to be the first known author in the territories ruled by the Arpads who identified Hungarians with Huns (however, such an identification was known in Europe from the beginning of the 10th century). Earlier, in the first decades of the 13th century, Attila was added to the genealogy of the ruling dynasty, even though there were statements in that century that excluded Attila and promoted Saint Stephen. This duality in the perception of Attila needs to be explained primarily by the pragmatism of the circles gathered around the royal court. The accounts known from other sources that link the motifs of the city, sword, and treasure of Attila with Hungary, once considered arguments proving the early development of a Hun-Hungarian identity there, arose outside the area of that monarchy and there is no indication that, except for the first account, they were known there. There is no evidence that shows the Archdeacon of Split knew at least the last two. Also, proper names and toponyms that resemble in terms of pronunciation, or in terms of spelling the name of Attila, recorded in the period preceding the creation of HISTORIA in testimonies in western Europe have nothing in common with the name of the ruler of the Huns. The identity of Huns and Hungarians, together with the references to both Attila as the ferocissimus persecutor christianorum (that could be understand as a synonym for flagellum Dei) and Hungarian invasions, all of which are to be found in Thomas’ work, seem to reflect the accounts of many medieval sources. At the same time, echoes of the last two motifs also appear in Hartvik’s LEGEND OF KING STEPHEN, which was known to Thomas.